2010
DOI: 10.1139/f09-194
|View full text |Cite
|
Sign up to set email alerts
|

When can we reliably estimate the productivity of fish stocks?

Abstract: In modern fishery stock assessments, the productivity of exploited stocks is frequently summarized by a scale-invariant “steepness” parameter. This parameter, which describes the slope of the spawner–recruit curve, determines resilience of a stock to exploitation and is highly influential when estimating maximum sustainable yield. In this study, we examined conditions under which steepness can be estimated reliably. We applied a statistical catch-age model to data that were simulated over a broad range of stoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 32 publications
1
57
0
Order By: Relevance
“…Estimation of the steepness of an SR curve is difficult even when natural mortality is constant within an assessment (Conn et al 2010). Often, parameters of the SR relationship require priors from meta-analysis or other information to allow estimation (Punt and Dorn 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of the steepness of an SR curve is difficult even when natural mortality is constant within an assessment (Conn et al 2010). Often, parameters of the SR relationship require priors from meta-analysis or other information to allow estimation (Punt and Dorn 2014).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, variations in survivorship (R/SSB) indicated that nearly 50% of variations year-class strength was within a 2-to 3-fold range of variation around the median. Taken together, these findings imply that variations in either growth or mortality rates required to generate such low levels of variability when integrated over the early life stages of development could be so subtle as to be nearly undetectable based on the levels of accuracy and precision normally associated with field-derived measurements of these vital rates (Conn et al 2010;Helbig and Pepin 1998;Maunder and Wong 2011). For example, a 5-to 10-fold variation in survivorship can be achieved by a 5% change in vital rates when approximately 99.99% of offspring are lost during the stage when recruitment is "set" (Beyer 1989).…”
Section: Stochastic Simulationsmentioning
confidence: 96%
“…They are important for estimating selectivity of fisheries and fisheryindependent surveys (Hilborn and Walters, 1992;Punt and Hilborn, 1997;Maunder and Punt, 2013;Maunder and Piner, 2015), and critical for the estimation of biological parameters such as natural mortality, recruitment variability, and growth (Chen et al, 2003;Conn et al, 2010;Szuwalski and Punt, 2012;Methot and Wetzel, 2013;Maunder and Punt, 2013;Kolody et al, 2015). Historically, many of these parameters, particularly those related to growth, were estimated externally and then used as fixed parameters in stock assessment models, due to the challenges in estimating them internally.…”
Section: Introductionmentioning
confidence: 99%